Effect of relationship quality on loyalty: the moderating role of personality traits among young fashion retail customer in Indonesia - Assad Diari Harumy; Rokhima Rostiani (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2021)
This research aims to analyze the effect of relationship quality on a fashion retail store customer's loyalty in Indonesia. We further investigate the moderating role of personality traits (innovativeness, variety seeking, and relationship proneness) on the relationship between relationship quality and loyalty. An online survey utilizing a questionnaire was conducted, purposively sampled to potential respondents resulting in 1.341 valid responses. All valid data were analyzed with structural equation modelling, including the moderating effect. The findings showed that relationship quality positively affects loyalty while only the innovativeness trait moderates the relationship between relationship quality and loyalty. This research suggests that fashion retail stores should increase the relationship quality with their customer by developing customer service with an excellent standard service procedure, conducting email and social media marketing, and creating a loyalty program that emphasizes the functional benefit. Further, innovation in terms of product is also vital to maintain the fashion retail store's loyalty.